Nucleocapsid single point-mutation associated with drop-out on RT-PCR assay for SARS-CoV-2 detection - Fernanda de Mello Malta; Deyvid Amgarten; Alexandre Rodrigues Marra; Roberta Cardoso Petroni; Luiz Henrique da Silva Nali; Ricardo Andreotti Siqueira; Miguel Cendoroglo Neto; Silvia Cassiano Oler; João Renato Rebello Pinho (BMC Infectious Diseases, 2023)
Abstract Background Since its beginning, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has been a challenge for clinical and molecular diagnostics, because it has been caused by a novel viral agent. Whole-genome sequencing assisted in the characterization and classification of SARS-CoV-2, and it is an essential tool to genomic surveillance aiming to identify potentials hot spots that could impact on vaccine immune response and on virus diagnosis. We describe two cases of failure at the N2 target of the RT-PCR test Xpert® Xpress SARS-CoV-2. Methods Total nucleic acid from the Nasopharyngeal (NP) and oropharyngeal (OP) swab samples and cell supernatant isolates were obtained. RNA samples were submitted to random amplification. Raw sequencing data were subjected to sequence quality controls, removal of human contaminants by aligning against the HG19 reference genome, taxonomic identification of other pathogens and genome recovery through assembly and manual curation. RT-PCR test Xpert® Xpress SARS-CoV-2 was used for molecular diagnosis of SARS-CoV-2 infection, samples were tested in duplicates. Results We identified 27 samples positive for SARS-CoV-2 with a nucleocapsid (N) gene drop out on Cepheid Xpert® Xpress SARS-CoV-2 assay. Sequencing of 2 of 27 samples revealed a single common mutation in the N gene C29197T, potentially involved in the failed detection of N target. Conclusions This study highlights the importance of genomic data to update molecular tests and vaccines.